Improving Students’ Ability to Memorize Short Surahs through the Card Sort (PBL) Strategy - Susanti, Feni (Jurnal Keprofesian Guru Keagamaan, 2025)
This study aims to improve students’ learning outcomes in Islamic Religious Education (IRE), particularly in developing understanding and moral awareness of Asmaul Husna (the Beautiful Names of Allah), through the implementation of the Problem-Based Learning (PBL) model. The research was conducted using a Classroom Action Research (CAR) approach, emphasizing collaborative learning and reflective cycles of planning, acting, observing, and reflecting. The participants consisted of fourth-grade students at SDN 005 Cemaga Selatan, Natuna Regency, Indonesia. Data were collected using tests, observation sheets, and documentation and analyzed both quantitatively and qualitatively. The findings indicate significant improvement in students’ cognitive and affective learning outcomes. The average test scores increased from 69.0 in the pre-cycle to 78.0 in Cycle I and 87.0 in Cycle II, while learning mastery improved from 60% to 100%. In addition, students demonstrated greater engagement, curiosity, and collaboration during classroom activities. The study concludes that the PBL model effectively enhances understanding and internalization of Islamic moral values by transforming the learning process from memorization-based to inquiry-based. It contributes to the ongoing discourse on integrating innovative pedagogies into Islamic education to promote holistic development encompassing faith, knowledge, and character (iman, ilmu, and akhlaq).